1974
DOI: 10.1021/jo00928a034
|View full text |Cite
|
Sign up to set email alerts
|

Steric and electrostatic interactions in reactions of carbohydrates. II. Stereochemistry of addition reactions to the carbonyl group of glycopyranosiduloses. Synthesis of methyl 4,6-O-benzylidene-3-O-methyl .beta.-D-mannopyranoside

Abstract: Notes 3-Vinyloxymethyl-l-methyl-2-pyridone (7) was prepared from 6 and ethyl vinyl ether using mercuric acetate as catalyst,12 yield 34% as a yellow oil: gc on 5% QF-1 on Chromosorb W 80/100, 10 ft X 0.25 in., 168°, retention time 6.4 min; nmr (CCU) S 7. 00-7.43

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Further-(la) (38) was converted into the 2-0-triflyl derivative (16) by more, it has actuated intensive efforts to develop improved reaction with trifluoromethanesulfonic anhydride (39). The remethods of synthesis, and especially procedures suitable for action of 1 6 with T A S F~ in dichloromethane occurred rapidly the preparation of 18F-labeled carbohydrates for use in medical in cold solution.…”
Section: Methyl46-0-benzylidene-3-o-methyl-~-~-mannopyranomentioning
confidence: 99%
“…Further-(la) (38) was converted into the 2-0-triflyl derivative (16) by more, it has actuated intensive efforts to develop improved reaction with trifluoromethanesulfonic anhydride (39). The remethods of synthesis, and especially procedures suitable for action of 1 6 with T A S F~ in dichloromethane occurred rapidly the preparation of 18F-labeled carbohydrates for use in medical in cold solution.…”
Section: Methyl46-0-benzylidene-3-o-methyl-~-~-mannopyranomentioning
confidence: 99%
“…These results parallel those of Miljković for sodium borohydride-mediated reduction of these substrates and may be rationalised by minimisation of dipole–dipole interactions in an early transition state. 16…”
Section: Resultsmentioning
confidence: 99%
“…These results parallel those of Miljković for sodium borohydride-mediated reduction of these substrates and may be rationalised by minimisation of dipole-dipole interactions in an early transition state. 16 The relative configuration of these compounds was tentatively assigned with the aid of NOE studies ‡ and confirmed for compound 18 by single crystal X-ray diffractometry (Fig. 1).…”
Section: Papermentioning
confidence: 87%